A randomized controlled 27 years follow up of three resin composites in Class II restorations. Issue 12 (December 2015) - Pallesen, Ulla; van Dijken, Jan W.V.
Abstract: Objective: To evaluate the durability of three conventional resin composites in Class II restorations during 27 years. Methods: Thirty participants, 25 female and 5 male (mean age 38.2 years, range 25–63), received at least three (one set) as similar as possible Class II restorations of moderate size. The three cavities were chosen at random to be restored with a chemical-cured (Clearfil Posterior) and two visible light-cured resin composites (Adaptic II, Occlusin). A chemical-cured enamel bonding agent (Clearfil New Bond) was applied after Ca(OH)2 covering of dentin and enamel etch. Marginal sealing of the restorations was performed after finishing. One operator placed 99 restorations (33 sets). Evaluation was performed with slightly modified USPHS criteria at baseline, 2, 3, 10 and 27 years. Results: Postoperative sensitivity was observed in 5 patients. Three participants with 11 restorations (11%) could not be evaluated at the 27 year recall. Thirty-seven restorations failed (13 AII, 10 CP and 14 O). The overall success rate after 27 years was 56.5% (AII 55.2%, CP 63.0%, O 51.7%; p  = 0.70), with an annual failure rate of 1.6%. The main reason for failure was secondary caries (54.1%), followed by occlusal wear (21.6%) and material fracture (18.9%). Non-acceptable color match was seen in 24 (28.3%) of the restorations (AII 2, CP 16, O 6). Cox regression-analysis showed significant influence of the covariates tooth type, caries risk, and bruxing activity of the participants. Conclusions: Class II restorations of the three conventional resin composites showed an acceptable success rate during the 27 year evaluation.